Selective modification of alkyne-linked peptides and proteins by cyclometalated gold(III) (C^N) complex-mediated alkynylation. Issue 7 (1st April 2020) - Ko, Hok-Ming; Deng, Jie-Ren; Cui, Jian-Fang; Kung, Karen Ka-Yan; Leung, Yun-Chung; Wong, Man-Kin
Graphical abstract: Abstract: Alkyne is a useful functionality incorporated in proteins for site-selective bioconjugation reactions. Although effective bioconjugation reactions such as copper(I)-catalyzed and/or copper-free 1, 3-dipolar cycloadditions of alkynes and azides are the most common approaches, the development of new alkyne-based bioconjugation reactions is still an ongoing interest in chemical biology. In this work, a new approach has been developed for selective modification of alkyne-linked peptides and proteins through the formation of arylacetylenes by a cross-coupling reaction of 6-membered ring cyclometalated gold(III) (C^N) complexes (HC^N = 2-arylpyridines) with terminal alkynes. Screening of the reaction conditions with a series of cyclometalated gold(III) complexes with phenylacetylene gave an excellent yield (up to 82%) by conducting the reaction in slightly alkaline aqueous conditions. The reaction scope was expanded to various alkynes, including alkyne-linked peptides to achieve up to >99% conversion. Using fluorescent dansyl (1l ) and BODIPY (1m )-linked gold(III) complexes, alkyne-linked lysozyme has been selectively modified.